ANALISIS DAYA SAING EKSPOR KOMODITI UNGGULAN NON MIGAS DI PROVINSI SUMATERA SELATAN - Trianto, Anton (Universitas Muhamamdiyah Metro, 2015)
This research aimed to analyze the level of competitiveness of 7 non-oil commodities of South Sumatera Province, namely rubber, palm oil (CPO), coal, wood and wood products, shrimp, coffee and tea. The secondary data are used in this research which are the export value of 7 non-oil comodities of South Sumatera and the value of national exports for the same commodity in 2005-2013 period. The method of analysis using calculation of the index RCA (Revealed Comparative Advantage). The results showed that only rubber and coal commodity that can be categorized as a commodity that has a fairly high competitiveness. While other non-oil commodities such as shrimp, tea and coffee has an average value of RCA who approached a value of 1, which means the commodities are not yet classified as having a good competitiveness, but commodities are very good to continue to be developed so that can increase its competitiveness capabilities in the future. Three other commodities, namely palm oil and wood / wood products, are included in the category of commodities that are less competitive.Â Keyword: Export, Non-oil commodities, Competitiveness